Development of Buck-Boost Dc-Dc Converter Using LNK3204 Linkswitch IC - Rosli, Farisha; Wahyu Mulyo Utomo, (Evolution in Electrical and Electronic Engineering, 2022)
A DC-DC Buck-Boost converter is usually used in power electronic devices such as step-up or step-down as DC supply voltage to produce the voltage level required by the device’s component. The complexity of the converter also can make the Buck-Boost system difficult to maintain. To solve the complexity in this DC-DC Buck-Boost converter is using LNK3204 IC which is a build-in offline switch IC. The main objective of this project is to analyze the performance of the output voltage ripple by developing a prototype for this circuit and to analyze DC output voltage based on feedback current. By using LNK3204 IC it will save space that the PWM signal has built-in in the IC. The testing result shows the buck-boost dc-dc converter using LNK3204 IC can work in both conditions with better output voltage ripple with different values of the control resistor.